System Rozwoju Regionalnego w warunkach Koncepcji Przestrzennego Zagospodarowania Kraju 2030 oraz Zrównoważonego Rozwoju Regionów w Polsce: The Regional Development System under the National Spatial Development Concept 2030 and the Sustainable Development of the Regions in Poland - Klimek, Anna; Klimek, Michał (Management and Administration Journal, 2021)
This work aims to introduce readers to aspects of the National Spatial Development Concept 2030 and the Sustainable Development of the Regions in Poland. The authors draw attention to the ongoing continuous processes of global change, leading to the rapid development of the local and the associated changes in quality management of public services and the Integrated Development System.